Paleoceanography of the southern Coral Sea across the Mid-Pleistocene Transition - Russon, Thomas Ford (The University of Edinburgh, 2011)
A comprehensive theory explaining the relationship between periodic variations in the Earths orbital parameters and the response of the climate system remains elusive. One of the key challenges is that of the Mid-Pleistocene Transition (MPT), during which the dominant mode of glacial/interglacial climatic variability shifted without any corresponding change in the mode of orbital forcing. Subtropical climate on orbital time-scales is sensitive to variability in both the low-latitude ocean/atmosphere circulation regime and the global carbon-cycle (through its effect on atmospheric greenhouse gas levels), both of which may have played a role in the shift in mode of global climate response to orbital forcing during the MPT. This thesis presents a series of multi-proxy (foraminiferal stable isotope and trace-metal) paleoceanographic reconstructions from the subtropical southwest Pacific, as seen in marine sediment core MD06-3018, from 2470m water depth and 23ºS in the New Caledonia Trough, southern Coral Sea. The core age-model, based upon magnetic stratigraphy and orbital tuning, yields a mean sedimentation rate at the site of 20mm/ka and a core-bottom age of 1600ka. The MD06-3018 reconstruction of New Caledonia Trough deep water chemistry, based on benthic 13C measurements, shows that the spatial chemistry gradient within the Southern Ocean between deep waters entering the Tasman Sea and the open Pacific was greater during glacial (relative to interglacial) stages over at least the past 1100ka. This gradient was, however, generally reduced on the >100kyr time-scale across the MPT, consistent with it being a period of reduced deep water ventilation in both hemispheres. The MD06-3018 Mg/Ca-derived reconstruction of subtropical southwest Pacific Sea Surface Temperature (SST) shows glacial/interglacial variability of 2-3ºC but no significant trends on the >100kyr time-scale over the duration of the record. An estimate of the uncertainty associated with the SST reconstruction demonstrates that no significant changes in reconstructed southern Coral Sea mean-annual SST can be identified between interglacial stages across the MPT. It is, therefore, unlikely that regional climatic change constituted the main cause for the observed middle Pleistocene expansion of coral reef systems. The >100kyr time-scale stability of southern Coral Sea SST means that the position of the southern boundary of the Pacific warm pool has also been stable over at least the past 1500ka. Comparison with other low-latitude Pacific reconstructions shows that the early Pleistocene warm pool was consequently more hemispherically asymmetric than its present configuration, with the latter being established by ~1000ka and implying significant changes in meridional atmospheric heat and moisture fluxes prior to the MPT. On orbital time-scales, the SST reconstruction shows a clear shift from dominant 40kyr to 100kyr modes of variability over the MPT, although significant 40kyr structure is also retained into the middle/late Pleistocene. In contrast, reconstructed hydrological cycle variability (based on coupled 18O-Mg/Ca measurements) shows only limited coherence with the obliquity cycle and a stronger relationship with the precession cycle. The decoupling of the reconstructed subtropical SST and hydrological cycle responses places constraints on the extent of orbitally paced fluctuations in the low-latitude ocean/atmosphere system. Instead, comparison of the MD06-3018 SST reconstruction with others from across the lowlatitude Pacific supports a dominant role for greenhouse gas forcing in low-latitude western Pacific glacial/interglacial SST variability across the Pleistocene. The subtropical multi-proxy climate reconstructions presented here show that the timing and sense of long-term (>100kyr time-scale) changes in the low-latitude ocean/atmosphere circulation regime are consistent with that system having been important in the expansion of northern hemisphere ice-volume during the early part of the MPT. However, the subtropical reconstructions also suggest that neither the low-latitude ocean/atmosphere circulation system nor the global carbon-cycle underwent a fundamental change in mode of response to orbital forcing during the transition. Instead, the origin of the 100kyr glacial/interglacial mode was most likely related to thresholds in the dynamics of the expanding northern hemisphere icesheets, leading in turn to the existence of significant inter-hemispheric asymmetry in the orbital time-scale climate response over the middle/late Pleistocene. Summary for Non-Specialists. Over the past five million years of its history, the Earths climate has undergone a series of regular, or nearly regular, fluctuations between warmer and colder states. These fluctuations take tens to hundreds of thousands of years to occur and are known as the ‘glacial/interglacial cycles’ on account of the associated changes in ice-sheet extent in the high-latitudes. The origin of these cycles is widely held to be the regular variations in form of the Earths orbit around the sun. In spite of decades of research, however, no complete ‘orbital theory of climate’ exists, mainly because the patterns of past climate variability, as reconstructed using ‘proxies’ for variables such as surface temperature, is much more complex than that of the orbital variations themselves. It follows that processes within the Earth system, especially those associated with large ice-sheets, the carbon-cycle and the ocean circulation system, act to substantially modify the climate response to the orbital variations. Over the past ten years, new observations from both ice-cores and low-latitude marine sediment cores have suggested that the dominant system(s) involved in setting the Earths response to the orbital variations may potentially be the carboncycle and/or the low-latitude ocean/atmosphere circulation regime rather than highlatitude ice-sheet dynamics, as was generally supposed previously. If this new view is correct, it has profound implications for the general sensitivity of the climate to the carbon-cycle on a range of time-scales - making its evaluation a scientific objective of considerable current importance. This thesis presents a series of reconstructions of aspects of climate and carbon-cycle variability for the subtropical southwest Pacific, as based on proxy measurements in a marine sediment core than spans the past 1,600,000 years at around 5000 year resolution. The key focus is on an interval called the ‘Mid- Pleistocene Transition’, during which time the mode of glacial/interglacial variability changed, indicating a fundamental change in one or more aspects of the response to the orbital forcing. The study site is well placed to investigate variability in both the carbon-cycle and low-latitude ocean circulation over the climatic transition as it lies between the Southern Ocean, a key source of carbon-cycle variability and the equatorial Pacific, where the modern El-Niño system arises. By characterizing variability in these systems, the potential role played by both systems in causing the change in mode of glacial/interglacial variability can be evaluated. The key findings of the thesis are that; firstly, changes in the long-term state of the low-latitude ocean circulation system may well have been important for the expansion of northern hemisphere ice-sheets during the early part of the Mid- Pleistocene Transition. Secondly, it provides further support for a close connection between variability in the carbon-cycle and low-latitude climate on orbital timescales but suggests that there is no clear evidence for either system undergoing a fundamental change in sensitivity to the orbital forcing during the transition. This implies that whilst paleoclimate records can potentially provide useful constraints on climate sensitivity to greenhouse gas forcing, it was the changing dynamics of the newly expanded northern hemisphere ice-sheets that led to the change in dominant glacial/interglacial periodicity during the Mid-Pleistocene Transition.
NER/S/A/2006/14325
Keywords: paleoceanography; Pleistocene; Pacific; sea surface temperature; orbital forcing; carbon cycle